Safety Stock, Warehouse Capacity, and Return of Goods in Inventory Model Development - Roland Y. H. Silitonga; Valyn Alanda Saputra; Aamir Khan (Journal of Novel Engineering Science and Technology, 2022)
With the increasing level of competition between companies, companies are required to be able to manage their inventory system optimally. In the pharmacy supply system, it is important to consider the uncertainty factor because the demand for medicines depends on the uncertain nature of the disease, besides that there is an expiration factor that must be considered because medicines must have an expiration date. To solve the problem of expiration, the supplier usually provides a return policy in accordance with the specified conditions. In addition, pharmacies also have limitations on warehouse capacity that must be considered. To solve the problem of limited warehouse capacity in this study, an approach to the requirements of the Karush Kuhn-Tucker method was used. From the developed model, two ordering times are obtained, namely and which will be compared to get the optimal ordering time. From the analysis of the model, it is found that the more characteristic considerations in an inventory system, the greater the total inventory cost.